Decision Support System for Determining the Head of Operations with Analytical Hierarchy Process Method - Yosefo Halawa; Jonson Manurung (Putaka Timur Publisher, 2021)
Implement existing policies leading and controlling all office operational activities, directing employees to make accountability reports for office operational activities to managers, supervising and approving transactions for each activity according to company needs. The problem that is being faced at the New Mitra Karya Cooperative Service office, Lubuk Pakam unit XXVII is the selection of the operational head which does not go through the appropriate stages and rules, but by direct election between family relationships. A decision support system based on computer based information systems (CBIS) that is able to adapt and can be developed to support providing solutions to a problem, one of which is the selection of operational heads using the AHP method. The concept of the Analytical Hierarchy Process (AHP) method is to find a comparison / summation of the weights of the work rating on each alternative. With a system that applies the AHP method, the results obtained are in the form of decisions in the selection of operational heads quickly and accurately.